2019
DOI: 10.1002/ccd.28390
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter mitral valve‐in‐valve implantation in a pediatric patient

Abstract: An 11-year-old girl, with 25 mm mosaic tissue valve presented with clinical and echocardiographic appearance of stenotic mitral valve prosthesis. Her condition was treated via a transcatheter valve-in-valve implantation using a 23 mm Edwards Sapien 3, with satisfactory outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A few studies have reported promising results regarding the feasibility, safety, and efficacy of hybrid Melody MVR [ 1–3 ]. However, based on a limited worldwide experience, Melody MVR may be considered a promising alternative in infants <1 year of age, either as a bridge to mechanical MVR, which can be performed safely at an older age [ 7 ], or as a bridge to further mitral Melody valve-in-valve implantation [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported promising results regarding the feasibility, safety, and efficacy of hybrid Melody MVR [ 1–3 ]. However, based on a limited worldwide experience, Melody MVR may be considered a promising alternative in infants <1 year of age, either as a bridge to mechanical MVR, which can be performed safely at an older age [ 7 ], or as a bridge to further mitral Melody valve-in-valve implantation [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…28 In 2016, J. Morgan et al published the first case of an 11-year-old patient with a failed mechanical mitral prosthesis requiring hybrid implantation of a 26 mm Edwards Sapien S3 valve mounted on a MEMO 3D annuloplasty ring. 29 Momenah et al published the first transcatheter TMVI of Edwards Sapien S3 in the pediatric age group 14 , a case included in this series.…”
Section: Discussionmentioning
confidence: 99%
“…One of the patients included in this study was previously published as a case report. 14 Patients recruited in this procedure included symptomatic patients with dysfunctional bioprosthetic valves with a weight above 20 kg. The primary outcome included successful implantation of the Edwards valve with no major complications.…”
Section: Ethics and Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation